The Relationship Between the Stock Market Volatility, Liquidity, Exchange Rate Return, and Stock Return During the COVID-19 Period: The case of the BIST 100 Index - Bulut, Emre; Simsek, Ahmed Ihsan (My University, 2023)
The COVID-19 Pandemic, emerged in China at the end of 2019, negatively affected many sectors on global scale. This study examined the period between March 11, 2020, when the first case was seen in Turkey, and May 23, 2022, when the pandemic measures were largely lifted. The study aims to research the relationship between stock exchange return, stock exchange volatility, liquidity, and exchange rate return; and to research the movement characteristics of selected variables in different regimes by using Markov Switching Method during the COVID-19 period. The results showed a negative correlation between the BIST-100 Index Return of Borsa Istanbul (BIST) and volatility and exchange rate returns. Simultaneously there is a positive correlation between the BIST-100 Index Return and liquidity. Furthermore, it has been determined that the data movements in the examined period occurred within the framework of two different regimes. It has been observed that the probability of the BIST-100 Index Return, volatility, and exchange rate returns to remain in the same regime is high, and the probability of switching from one regime to another is relatively low.
Keywords: BIST; Volatility; emerging markets; exchange rate; stock return